Аналіз антенних систем управління БПЛА - Домарєв, А. С. (ХНУРЕ, 2024)
This study provides analysis of antenna systems used in unmanned aerial vehicles (UAVs). The research explores various types of antennas, their characteristics, and applications in the UAV industry. The practical significance of this research lies in enhancing the efficiency and safety of UAV operations across diverse fields. By selecting the most suitable antenna system, UAV manufacturers and operators can improve communication reliability, extend operating ranges, and enhance overall performance. This study serves as a valuable resource for engineers, researchers, and professionals involved in UAV technology development and implementation.
Keywords: БПЛА; аналіз антенних систем